The social impact of the Normal School for Teachers of Santa Clara (1916-1940) (Islas, 2023)
Introduction: The Normal Schools were among the most notable educational institutions of the entire Cuban society during the republican period, for which the objective was to explain the social impact of the Normal School for Teachers of Santa Clara between 1916 and 1940.Methods: The documentary analysis method was used; as well as the historical-logical, analytical-synthetic and inductive-deductive.Results: It was demonstrated, through documentary sources, that the Normal School for Teachers of Santa Clara had a strong social impact in the period addressed, both from the curricular and the extracurricular, with the training of prepared teachers and the dissemination of knowledge in the most diverse layers of the Villareña and Cuban society in general.Conclusions: The Normal School of Santa Clara contributed to renewing teaching, disseminated notions of health, hygiene, morality and culture to the whole of society, provided artistic displays in different branches and forged a culture of resistance among normal students.
Keywords: Normal School; social impact; Santa Clara